WAYS TO EVALUATE THE RESULTS OF THE ORGANIZATION'S EMPLOYEES AND INCREASE THEIR PRODUCTIVITY IN THE CONDITIONS OF THE MARKET ECONOMY - Maya Nutfullayevna Khalilova; Polotov Shokhrukh Shavkatovich (Scholars Digest Publishing, 2023)
The performance of the HR process needs to be assessed to improve the effectiveness of organizations. Approaches to determining indicators of economic and social efficiency of an organization’s personnel are considered. Tools for determining personnel activities are presented. The characteristics of these tools are given and their use is considered within the framework of studying the effectiveness of the organization’s personnel management process.
Keywords: effect, efficiency, process, organization, personnel management, assessment tools